REQUIRED FUTURE CAPACITY ANALYSIS (Perner's Contacts, 2018)
This paper pursues the chosen airline network analysis (Air France) and it contains information about the main hub, current fleet operated, numbers of passengers carried over last five years and also the visualisation of the airline network for short and long-haul flights based on a leg distance; with the focus on the key (strategy) routes. The case study also focuses on the estimation of required future capacity – as the passenger number will grow, the load factor will be increasing, but in reality, it will just rarely reach more than 90 percent. The estimated number of new planes that will be required in a future by a chosen airline are also incorporated. The very last part is dedicated to recommendations for the airline marketing strategy in connection to their further cooperation with the biggest player on the airplane´s worldwide production on the market, Airbus company.